2015
DOI: 10.1523/jneurosci.1593-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Polarity Protein Pals1 Regulates Radial Sorting of Axons

Abstract: Myelin is essential for rapid and efficient action potential propagation in vertebrates. However, the molecular mechanisms regulating myelination remain incompletely characterized. For example, even before myelination begins in the PNS, Schwann cells must radially sort axons to form 1:1 associations. Schwann cells then ensheathe and wrap axons, and establish polarized, subcellular domains, including apical and basolateral domains, paranodes, and Schmidt-Lanterman incisures. Intriguingly, polarity proteins, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
17
2
1
Order By: Relevance
“…Epithelial-like cell polarization is essential during Schwann cell myelination and in particular in the control of the geometric parameters evident in the mature myelin sheath ( Masaki, 2012 ). The first evidence of the role of polarity proteins during SC myelination was established in pre/early myelinating cells whereby Pals1, Par3, and LKB1 facilitates the polarization of E-cadherin and p75 receptor in the glial membrane, directly adjacent to the axon ( Chan et al, 2006 ; Shen et al, 2014 ; Zollinger et al, 2015 ). This first polarization step is critical to initiate the myelin sheath wrapping of the axon.…”
Section: Epithelial-like Polarization and Geometry Of The Myelin Sheamentioning
confidence: 99%
“…Epithelial-like cell polarization is essential during Schwann cell myelination and in particular in the control of the geometric parameters evident in the mature myelin sheath ( Masaki, 2012 ). The first evidence of the role of polarity proteins during SC myelination was established in pre/early myelinating cells whereby Pals1, Par3, and LKB1 facilitates the polarization of E-cadherin and p75 receptor in the glial membrane, directly adjacent to the axon ( Chan et al, 2006 ; Shen et al, 2014 ; Zollinger et al, 2015 ). This first polarization step is critical to initiate the myelin sheath wrapping of the axon.…”
Section: Epithelial-like Polarization and Geometry Of The Myelin Sheamentioning
confidence: 99%
“…In the second report, Shen et al found that regardless of any metabolic functions, LKB1 deletion in SCs compromises the proper localization of the critical cell polarity protein Par‐3, which has been previously proposed to be important for myelination in an in vitro co‐culture system . However, given that the in vivo functions of Par‐3 and other polarity components in SCs are likely redundant, it is conceivable that abnormal localization of Par‐3 may have arisen because of the metabolic abnormalities in crippled SCs, and Par‐3 inactivation, per se , does not contribute to the dysmyelination observed. In this respect, it would be important in the future to characterize nerve development and myelination in conditional mutants lacking Par‐3 in SCs.…”
Section: Perinatal Lkb1 Disruption In Scs Impairs Myelinationmentioning
confidence: 99%
“…Thus, Pals1 transiently colocalizes with Par‐3 at the adaxonal Schwann cell membrane then in the paranodes and clefts (Ozcelik et al, ; Poliak et al, ; Zollinger, Chang, Baalman, Kim, & Rasband, ) where they form a biochemical complex (Zollinger, Chang, et al, ). Knockout/knockdown studies indicate Pals1 is required for the timely onset of Schwann cell myelination and the fidelity of radial sorting of axons (Ozcelik et al, ; Zollinger, Chang, et al, ). Future studies to determine whether Necl‐4 recruits the full Par‐3 polarity complex to the adaxonal membrane as well as other components of the Crumbs complex, in addition to Pals1, will be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%